Bifunctional bispidine derivatives for copper-64 labelling and positron emission tomography. Issue 6 (24th January 2017) - Roux, Amandine; Gillet, Raphaël; Huclier-Markai, Sandrine; Ehret-Sabatier, Laurence; Charbonnière, Loïc J.; Nonat, Aline M.
Abstract : A bispidine cage coordinates 64 Cu 2+ rapidly and quantitatively at room temperature, and biotin and maleimide functions allow for targeted PET imaging. Abstract : The first radiolabelling studies of a bispidine (3, 7-diazabicyclo[3.3.1]nonane) derivative substituted by a glycinate pendant arm (L1 ) with 64 Cu are reported. Labelling was fast and easily performed at room temperature and in a wide range of pH values. Under these conditions, radiochemical yields over 90% were achieved within 5 minutes at micromolar concentration of the ligand. A bifunctional analogue ofL1 (L2 ) has been obtained by introducing anl -lysine amino acid on the bispidine skeleton. LigandL2 demonstrates good radiolabelling capacities at room temperature and in water (pH 4 to pH 6). This new bispidine is a versatile platform which can easily react with NHS esters and can be subsequently coupled to a recognition unit in order to perform targeted Positron Emission Tomography (PET) imaging. As a proof of concept, two new bifunctional chelators (BFCs) with a biotin (L3 ) or a maleimide functional group (L4 ) have been synthesized. The biotinylated BFC is very valuable for pretargeting strategies using streptavidin-conjugated antibodies. The reactivity of the maleimide derivativeL4 has been studied with the model peptide GP120. Quantitative coupling has been achieved under physiological conditions, showing a good regioselectivity towards cysteine residues versus lysine amino acids.